Simplified development of multiplex real-time PCR through master mix augmented by universal fluorogenic reporters. (September 2016) - Wadle, Simon; Lehnert, Michael; Schuler, Friedrich; Köppel, René; Serr, Annerose; Zengerle, Roland; von Stetten, Felix
Mediator probe (MP) PCR is a real-time PCR approach that uses standardized universal fluorogenic reporter oligonucleotides (UR) in conjunction with label-free sequence-specific probes. To enable multiplex real-time MP PCR, we designed a set of five optimized URs with different fluorescent labels. Performance of the optimized URs was verified in multiplex real-time MP PCR for the detection of a pentaplex food panel and a quadruplex methicillin-resistant Staphylococcus aureus ( MRSA) panel. Results were comparable to corresponding multiplex hydrolysis probe (HP) PCR, also designated as TaqMan PCR. Analyses of MRSA DNA standards and DNA extracted from patient swab samples showed improved lower limits of detection (LoDs) by a factor of 2–5 when using quadruplex real-time MP PCR instead of HP PCR. The novel set of standardized URs we present here simplifies development of multiplex real-time PCR assays by requiring only the design of label-free probes. In the future, real-time PCR master mixes could be augmented with up to five standardized fluorogenic URs, each emitting light at a different wavelength.